2001
DOI: 10.1007/s004320000208
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography with 2-[18F]-fluoro-2-deoxy-D-glucose in oncology

Abstract: Positron emission tomography (PET) using 18F-fluorodeoxyglucose (FDG) is considered to be a very useful adjunct to anatomic imaging techniques and is now primarily used for oncological indications. These indications include diagnosis, staging, and therapy monitoring. In this review, we discuss the articles in which FDG-PET is clinically used for monitoring therapy in lung and colorectal tumours, head and neck cancer, sarcoma, and hepatocellular carcinoma. It is found that the amount of FDG uptake strongly corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(5 citation statements)
references
References 45 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…The uptake mechanism and biochemical pathway of 18F-FDG metabolism has been extensively studied in vitro and in vivo ; transport through cell membrane via glucose transporter isoform 1 (GLUT1) and intracellular phosphorylation by hexokinase (HK) have been identified as key steps for subsequent accumulation in HCC. 8 9 10 11 12 13 Many studies have shown upregulation of GLUT1 in HCC, but not in non-tumor liver tissue. 14 15 Amann, et al 15 demonstrated a positive correlation between GLUT1 expression and Ki-67 labeling index in patients with HCC, suggesting that its expression is associated with advanced tumor stage and poor differentiation.…”
Section: Clinical Applications Of Metabolic Imaging In Hccmentioning
confidence: 99%
“…The uptake mechanism and biochemical pathway of 18F-FDG metabolism has been extensively studied in vitro and in vivo ; transport through cell membrane via glucose transporter isoform 1 (GLUT1) and intracellular phosphorylation by hexokinase (HK) have been identified as key steps for subsequent accumulation in HCC. 8 9 10 11 12 13 Many studies have shown upregulation of GLUT1 in HCC, but not in non-tumor liver tissue. 14 15 Amann, et al 15 demonstrated a positive correlation between GLUT1 expression and Ki-67 labeling index in patients with HCC, suggesting that its expression is associated with advanced tumor stage and poor differentiation.…”
Section: Clinical Applications Of Metabolic Imaging In Hccmentioning
confidence: 99%
“…Subsequently, 2-DG at a therapeutic dose causes ATP depletion as well as oxidative stress and eventually facilitates cell death [21,22]. Moreover, these features of 2-DG in combination with the increased glucose uptake in cancer cells provide the rationale for the detection of tumors by positron emission tomography (PET) using 18 F-labeled 2-deoxy-D-glucose (FDG) [23,24]. …”
Section: Targeting Cancer Metabolismmentioning
confidence: 99%
“…To compensate for the inefficient ATP production, most tumors have an increased rate of glucose uptake. This property makes PET a highly sensitive and specific clinical tool to identify primary and metastatic lesions [35,36]. This technique uses the glucose analogue tracer 18 Fluorodeoxyglucose (FdG) to image and quantify glucose uptake, which has been found to be correlated with poor prognosis and to be highly dependent on the glycolytic rate [17,35,36].…”
Section: Glucose Metabolismmentioning
confidence: 99%